End-to-end QoS provisioning in future cognitive heterogeneous networks - Xiangying Dong; Jiajia Wang; Yong Zhang; Mei Song; Ruijun Feng (2009 IEEE International Conference on Communication Technology and Applications, 2009)
The cognitive network, which is based on the theory of cognitive radio, is undergoing rapid growth. But the research on QoS provisioning for cognitive heterogeneous networks is scarce. In this paper, an end-to-end QoS provisioning model is proposed withthe cognitive process. QoS mapping of different cognitive QoS domains in SLSs and the related resource provisioning signaling are also expounded. The proposed schemes can take use of the feedback on current network conditions, find or even predict the bottleneck of the network performance, take some reactions in advance, like changing QoS priority, and finally provide end-to-end QoS guarantee.